Contemporary architect’s self-education on the issues concerning architecture history. Selected problems - CHRZANOWSKA, OLGA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Olga Chrzanowska, Contemporary architect’s self-education on the issues concerning architecture history. Selected problems. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 403-417. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.17 The aim of this text is to describe the risks faced by contemporary architects when undertaking to learn, either directly or indirectly, about architecture in the era of the Internet and mass consumption of culture. The role of architect’s self-education on the issues concerning architecture history and aesthetic empathy theory in the context of everyday architectural landscapes. As an example, the historical foundations for the thinking on modernity in designs of the three architects: Peter Zumthor, Christian de Portzamparc and David Chipperfield